Assessment of quality of life in type II diabetic patients using the modified diabetes quality of life (MDQoL)-17 questionnaire (Brazilian Journal of Pharmaceutical Sciences, 2017)
Diabetic complications, comorbidities, and cost of treatment affect the quality of life (QoL) of an individual. The QoL assessment is considered an important measure of outcome in chronic disease management. The objective of our study was to assess the quality of life in Type II diabetes mellitus patients with and without complications using the modified diabetes quality of life (MDQoL)-17. A prospective descriptive study was conducted over 6 months, after taking ethical committee approval. As per the inclusion criteria from medicine wards of tertiary care hospital, 250 patients were selected. Demographic characteristics were documented in the data collection form and the patients were administered with the MDQoL questionnaire in different languages. The data was analyzed using IBM SPSS version 20. Majority of the patients were male (64.4%). The average age of the study population was 60.34±12.04 years. Most of the patients had a diabetes history of more than 10 years and HbA1c >; 8%. The average QoL score was 65.47±15.07. Majority of the diabetic patients had the QoL score between 70 and 50. Patients without complication had a better QoL. As the number of complications increased, there was a decrease in the QoL. The presence of comorbidity also decreased the QoL. There was a statistically significant correlation with various parameters such as age, duration of diabetes history, HbA1c, number of complications and type of complication verses QoL of diabetic patients (p